OsHAC1;1 and OsHAC1;2 Function as Arsenate Reductases and Regulate Arsenic Accumulation. Issue 3 (4th October 2016) - Shi, Shulin; Wang, Tao; Chen, Ziru; Tang, Zhong; Wu, Zhongchang; Salt, David E.; Chao, Dai-Yin; Zhao, Fang-Jie
Abstract : OsHAC1;1 and OsHAC1;2 function as arsenate reductases that play an important role in restricting As accumulation in rice shoots and grain when plants are exposed to arsenate. Abstract: Rice is a major dietary source of the toxic metalloid arsenic (As). Reducing its accumulation in rice ( Oryza sativa ) grain is of critical importance to food safety. Rice roots take up arsenate and arsenite depending on the prevailing soil conditions. The first step of arsenate detoxification is its reduction to arsenite, but the enzyme(s) catalyzing this reaction in rice remains unknown. Here, we identify OsHAC1;1 and OsHAC1;2 as arsenate reductases in rice. OsHAC1;1 and OsHAC1;2 are able to complement an Escherichia coli mutant lacking the endogenous arsenate reductase and to reduce arsenate to arsenite. OsHAC1:1 and OsHAC1;2 are predominantly expressed in roots, with OsHAC1;1 being abundant in the epidermis, root hairs, and pericycle cells while OsHAC1;2 is abundant in the epidermis, outer layers of cortex, and endodermis cells. Expression of the two genes was induced by arsenate exposure. Knocking out OsHAC1;1 or OsHAC1;2 decreased the reduction of arsenate to arsenite in roots, reducing arsenite efflux to the external medium. Loss of arsenite efflux was also associated with increased As accumulation in shoots. Greater effects were observed in a double mutant of the two genes. In contrast, overexpression of either OsHAC1;1 or OsHAC1;2 increased arsenite efflux, reduced As accumulation, and enhanced arsenate tolerance. When grown under aerobic soil conditions, overexpression of either OsHAC1;1 or OsHAC1;2 also decreased As accumulation in rice grain, whereas grain As increased in the knockout mutants. We conclude that OsHAC1;1 and OsHAC1;2 are arsenate reductases that play an important role in restricting As accumulation in rice shoots and grain.